Konsep Tafakkur Dalam Alquran Dalam Menyikapi Coronavirus Covid-19 - Indriya Indriya (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2020)
Abstract:Tafakkur in Arabic is interpreted as an act of thinking to bridge the perceptions and conceptions of this world life to the afterlife, and from creatures to their Creator, namely Allah. Tafakkur goes beyond this life to a wider region, the hereafter, and transcends the superficiality of materialism to a deeper horizon, that is